Epithelial––mesenchymal transition in hepatocellular carcinoma. (October 2009) - van Zijl, Franziska; Zulehner, Gudrun; Petz, Michaela; Schneller, Doris; Kornauth, Christoph; Hau, Mara; Machat, Georg; Grubinger, Markus; Huber, Heidemarie; Mikulits, Wolfgang
The transition of epithelial cells to a mesenchymal phenotype is of paramount relevance for embryonic development and adult wound healing. During the past decade, the epithelial––mesenchymal transition (EMT) has been increasingly recognized to occur during the progression of various carcinomas such as hepatocellular carcinoma (HCC). Here, we focus on EMT in both experimental liver models and human HCC, emphasizing the underlying molecular mechanisms which show partial recurrence of embryonic programs such as TGF-ββ and Wnt/ ββ-catenin signaling, including collaboration with hepatitis viruses. We further discuss the differentiation repertoire of malignant hepatocytes with respect to the potential acquisition of stemness, and the involvement of the mesenchymal to epithelial transition, the reversal of EMT, in cancer dissemination and metastatic colonization. The strong evidence for EMT in HCC patients demands novel strategies in pathological assessments and therapeutic concepts to efficiently combat HCC progression.